Composite Score Is a Better Reflection of Patient Response to Chronic Pain Therapy Compared With Pain Intensity Alone. Issue 1 (27th June 2020) - Pilitsis, Julie G.; Fahey, Marie; Custozzo, Amanda; Chakravarthy, Krishnan; Capobianco, Robyn
Abstract: Objective: The pain Numeric Rating Scale (NRS) score became standard when pain was introduced as the fifth vital sign in the 1990s. Although plagued with issues, it remains the basis for primary outcome measures in clinical trials for chronic pain therapies. Multidimensional composite scoring that considers all aspects of the chronic pain experience may provide a more meaningful response measure. Herein we propose a multidimensional responder index. Materials and Methods: Data were extracted from an ongoing prospective, multicenter study on DeRidder Burst spinal cord stimulation (B‐SCS) for chronic back and/or leg pain (NCT03082261). The analysis cohort consisted of subjects who completed the NRS, Pain Catastrophizing Scale (PCS), EuroQol‐5D (EQ‐5D), and eight‐item Patient‐Reported Outcomes Measurement Information System Physical Function preoperatively and at 12 months after implant. Results: A principal component analysis showed that each of the four measures contributed equally to the variance in the data set, confirming that pain score should not be used alone. Subjects who failed to respond on NRS responded on both PCS and EQ‐5D. Eighty‐one percent of subjects responded on at least two measures. The responder algorithm yielded an 84% success rate at both 6‐ and 12‐month time points. Conclusions: Our study suggests that therapeutic response, similar to the chronic pain experience, is multidimensional. Careful consideration should be made to incorporate composite endpoints in future SCS clinical trials.